Mexico : Basel Core Principles - Detailed Assessment of Observance - International Monetary Fund; World Bank (World Bank, Washington, DC, 2014)
This detailed assessment of the current state of implementation of the Basel core principles in Mexico has been completed as part of a financial sector assessment program update undertaken jointly by the International monetary fund and the World Bank. The assessment was conducted in September 2011 to update the 2006 assessment. It reflects the banking supervision practices of the country as of end-July 2011. Moreover, the bar to measure the effectiveness of a supervisory framework was raised following the recent financial crisis. The assessment is based on several sources: 1) a self-assessment in August 2011 by the country authorities, including written answers to an exhaustive questionnaire; 2) detailed interviews with staff from the relevant national agencies, including the CNBV (Comision Nacional Bancaria y de Valores), the Central Bank of Mexico (BoM), the SHCP (Secretaria de Hacienda y Credito Publico), and the Financial Intelligence Unit (UIF); 3) relevant laws, directives, circulars and guidelines, which constitute the regulatory framework; 4) relevant official pronouncements and other documentation on the supervisory framework; 5) primary evidence on the nature and extent of the supervisory practices; 6) sundry information on the structure and development of the country's financial sector, and more specifically, the country's banking sector; and 7) meetings with selected banks, auditing firms, and rating agencies. The assessment was performed in accordance with the guidelines set out in the core principles methodology, and assessed compliance with the 'essential' criteria only. The assessment of compliance with each principle is made on a qualitative basis. A four-part assessment system is used: compliant; largely compliant; materially noncompliant; and noncompliant. The assessors enjoyed excellent cooperation with their counterparts, and received all the information required.